STUDY OF CHARACTERIZATION AND GRAVITY CONCENTRATION USING JIG AND SHAKING TABLE OF SKARN AND OXIDE CLAY TYPE OF PRIMARY TIN ORE FORM BATUBESI, BELITUNG - RAFINIKA - Nim: 12514017 , YOGA
Tin consumption continues to increase over time as its use increases in the downstream industry. Indonesia ranks second largest as a producer of tin, with an estimated 70,900 tonnes of tin mined by 2015. Tin production in Indonesia can not be separated from the existence of PT Timah Tbk. One of the developments conducted by PT Timah Tbk is mining at Batubesi, Belitung in which the tin ore is categorized as primary ore. This tin primary ore is comprised of three types of ore with different characteristics, namely greisen, skarn, and oxide clay type ores. As the mining of this primary tin ores have to be carried out, the concentration process of the ores need to be established too. Researches related to the characterization of the primary ores, especially for skarn and oxide clay types and the study of gravitational concentration become important to perform. The initial stages of the research were the ore preparation of the run of mine (ROM), so that it would ready to be characterized and concentrated by gravity. The preparations were size reduction for skarn and drying for oxide clay. The prepared ores were characterized using XRD, XRF, and mineragraphic observations. The assay of the ore elements at certain sizes were also analyzed using XRF (size by size analysis). The ores were concentrated by gravity concentration using jig and shaking table at variations of P80 size of feeds of 297 µm, 210 µm, 149 µm, and104 µm, at variations in feed size fractions of -297 +210 µm, -210 +149 µm, -149 +104 µm, and -104 +62 µm for skarn type ores, and at variation of feed size fraction of -297 µm, -210 µm, -149 µm, and -104 µm for oxide clay type ore. Characterization of ore showed the Sn assay in the head grade of skarn was 0.25% and for oxide clay was 0.56%. In the gravitational concentration, the optimum P80 size was 212 µm for the process using jig and 149 µm for shaking table, the process using jig gave Sn recovery of 20.12%, the Sn assay was 0.25%, and the enrichment ratio was 1.06, the process using shaking table gave Sn recovery of 7.43%, the Sn assay was 0.36%, and the enrichment ratio was 1.5. The feed’s size fraction of -297 +212 µm gave optimum result in the experiment using jig and feed’s size fraction of -104 +62 µm in experiment using shaking table, jig gave Sn recovery of 59,5%, the Sn assay was 0,29%, and the enrichment ratio was 1.3, the process using shaking table gave the Sn recovery of 3.5%, the Sn assay was 1.3%, and the enrichment ratio was 6.3. In the oxide clay type, feed’s size fraction of -297 µm gave the optimum result of the experiment using jig and feed’s size fraction of -212 µm using shaking table, jig gave Sn recovery of 1,57%, the Sn assay was 1,32%, and the enrichment ratio was 1.91, the process using shaking table gave Sn recovery of 5.10%, the Sn assay was 4.56%, and the enrichment ratio was 8.3.